Penerapan Model Pembelajaran Cooperatif Learning dalam Meningkatkan Kompetensi Paedagogik Guru Matematika Kelas VI melalui Pembinaan Pengawasan di Kecamatan Sekongkang Tahun Pelajaran 2019-2020 - Wahiddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This supervisory action research (PTKp) aims to find out the extent of supervisors' guidance to improve the ability of teachers to apply cooperative learning models of mathematics learning for VI-grade elementary school in Sekongkang District. In the supervisory action research (PTKp) is carried out in 3 cycles, the results of the actions taken are proven to be able to improve teacher performance by achieving ideal standards. From 58.89% in the first cycle, it can increase to 69.33% in the second cycle, and the third cycle 77.89%. The results of this action research show that supervisors can improve teacher performance in developing cooperative learning of elementary school sixth- grade mathematics learning with completeness reaching 100%.